Inovasi Pembelajaran Digital Menulis Puisi melalui Media Canvapoet pada Siswa Kelas VII SMPN 1 Pragaan Sumenep - Jamilah, Kamilatun; Alatas, Mochammad Arifin; Susanti, Aria Indah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The rapid development of digital technology opens up opportunities for teachers to present learning media that are more interactive and relevant to the characteristics of the digital generation. This study aims to describe the implementation of Canvapoet media in learning to write poetry for seventh grade students of SMPN 1 Pragaan. The method used is descriptive qualitative with observation and interview techniques. The research subjects were seventh grade students, while the focus of the research object was directed at changes in the structure and aesthetics of poetry after the application of CanvaPoet media. Data analysis techniques were carried out following the Miles and Huberman model, which includes three important stages, namely; Data reduction, Data presentation and Conclusion drawing. The results of the study showed a significant increase in student interest and creativity, especially in aspects of diction, imagery, and better poetry organization. CanvaPoet also encourages students to dare to express themselves through a combination of text and visual elements. Obstacles such as limited internet access and technical capabilities can be overcome through intensive guidance and gradual learning. The conclusion of this study is that CanvaPoet is an effective digital learning innovation for developing students’ multiple intelligences and supporting sustainable literacy learning.Perkembangan teknologi digital yang pesat membuka peluang bagi guru untuk menghadirkan media pembelajaran yang lebih interaktif dan relevan dengan karakteristik generasi digital. Penelitian ini bertujuan untuk mendeskripsikan implementasi media Canvapoet dalam pembelajaran menulis puisi pada siswa kelas VII SMPN 1 Pragaan. Metode yang digunakan adalah deskriptif kualitatif dengan teknik observasi dan wawancara. Subjek penelitian adalah siswa kelas VII, sementara fokus objek penelitian diarahkan pada perubahan struktur dan estetika puisi setelah penerapan media CanvaPoet. Teknik analisis data dilakukan dengan mengikuti model Miles dan Huberman, yang meliputi tiga tahap penting yaitu;Reduksi data,Penyajian data dan Penarikan kesimpulan. Hasil penelitian menunjukkan adanya peningkatan signifikan dalam minat dan kreativitas siswa, terutama pada aspek diksi, imaji, serta pengorganisasian puisi yang lebih baik. CanvaPoet juga mendorong siswa untuk berani berekspresi melalui kombinasi teks dan elemen visual. Kendala seperti keterbatasan internet dan kemampuan teknis dapat diatasi melalui bimbingan intensif dan pembelajaran bertahap. Simpulan dari penelitian ini adalah bahwa CanvaPoet merupakan inovasi pembelajaran digital yang efektif untuk mengembangkan kecerdasan majemuk siswa serta mendukung pembelajaran literasi yang berkelanjutan.